(untitled) (International Seven Journal of Health Research, 2023)
Sedentary behavior, associated with little Physical Activity (PA) and inadequate habits, has contributed to the development of health problems in workers in developed and developing countries. Thus, the work environment seems to be an important space for the incorporation of appropriate health behaviors. This is a cross-sectional, exploratory and descriptive epidemiological study. The objective was to analyze the association of Leisure Time Physical Activity (LTPA) with Common Mental Disorders (CMD) and stress stages, considering issues related to work, sociodemographic, psychosocial characteristics and life habits of teachers from a public university in Bahia. The chi-square test was used to analyze the association between the study variables, CMD, stress and LPA considering the associations statistically significant when p-value ≤ 0.05. The results found regarding the prevalence of CMD was 20.4 for the population investigated. The presence of stress was positive for 24.0%. When categorized by phase, 3.6% were in the alert phase of stress; 24% in the resistance phase and 3.0% in exhaustion. The main results found in this study establish relationships with teaching work, stress, CMD, leisure and physical activities, demonstrating an association between these objects and the perception of health and quality of life of the teaching worker. Thus, it is important to develop policies to encourage the practice of PA within the workspaces of teachers, which can contribute to greater adherence to the practice and substantial improvement in the overall quality of life, in the physical and psychological domains and to reduce the symptoms of CMD and stress in this population.